Bronchopulmonary lesions due to aspiration of whole nutrition mixtures - Valiñas, Roberto; Palumbo, Alvaro; Rosano, Ernesto; Keuchkerián, Marcel; Keuchkerián, Sandra; Fernández, Isabel; Bertullo, Hugo (Cirugía del Uruguay, 1995)
Even if not very frequent, the aspira/ion of nutritional mixtures to the bronchial tree does exist. The absence of up-to-date literature on the anatomopathological impact of new industrial nutritional mixtures motivated the following study. lntra-trachea/ injections of bacteriologically controlled Ensure Abbott mixture who carried out in 24 Wister strain homocygotic rats. The injections were main at variable time intervals and increasing doses.